ANALISIS PELANGGARAN APOTEKER DI RUMAH SAKIT PADA KASUS ADMINISTRASI ERROR BERUJUNG PIDANA - I Gusti Ayu Dhea Arlitadelina; Anggraeni Endah Kusumaningrum (Masyarakat Hukum Kesehatan Indonesia, 2022)
Medication Error described as a sequence of events or cases that cause failure in the treatment process or therapeutic process that has the ability to threaten the patient in the treatment process. In Indonesia, there are numerous cases of Medication Errors, particularly in hospitalization, Fatal Incidences related to the use of drugs (Medication Errors) as many as twenty-six percent of incidents (26%) and of all these incidents, ME most frequently occurs in Administration phase 81.32%. The objective of this study is to determine the criminal sanctions in the case of Medication Error. The research method that is used in the research is normative method with a written rule of law approach. Primary materials include written legal rules, the secondary legal basic materials include journals or articles and tertiary materials related to the development of cases that are discussed and combined with perspectives from the researcher's point of view. ME cases can be resolved by Law of the Republic of Indonesia Number Thirty Six of 2014 concerning Health Workers, Criminal Provisions Article 84 Part A or B depending on the severity of the case.